Pengaruh Model Discovery Learning Berbantuan Alat Praktikum Fluida Dinamis terhadap Penguasaan Konsep dan Kemampuan Berpikir Kreatif Peserta Didik - Armini, Armini; Taufik, Muhammad; Kosi,; Zuhdi, Muhammad (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Concept mastery and creative thinking skills are essential competencies that students must possess to support effective problem-solving. This study aims to analyze the effect of the discovery learning model assisted by dynamic fluid practicum tools on concept mastery, creative thinking skills, and both simultaneously. The method employed was a quasi-experimental design using a non-equivalent control group design. The research sample consisted of two classes: class XI MIPA 1 as the experimental group and class XI MIPA 4 as the control group, selected through purposive sampling. The instrument for measuring concept mastery consisted of 10 multiple-choice questions, while creative thinking skills were assessed using 6 essay-type questions. Both instruments had been tested for validity, reliability, difficulty level, and discriminating power. Posttest data were analyzed using normality and homogeneity tests, followed by hypothesis testing using the t-test with pooled variance and MANOVA. The t-test results for concept mastery and creative thinking skills were 2.80 and 2.09, respectively, with a t-table value of 2.00 at a 5% significance level (0.05). These results indicate that tcount > ttable for both variables, meaning that H01 and H02 were rejected and Ha1 and Ha2 were accepted, demonstrating the effect of the discovery learning model assisted by practicum tools on both concept mastery and creative thinking skills. Furthermore, the MANOVA test yielded a significance value of 0.008 < 0.05, leading to the rejection of H03 and acceptance of Ha3, indicating a simultaneous effect of the discovery learning model assisted by practicum tools on concept mastery and creative thinking skills. Thus, the discovery learning model is effective in improving concept mastery, creative thinking skills, and both simultaneously.